Molecular mechanism of different flower color formation of Cymbidium ensifolium - Ai, Ye; Zheng, Qing-Dong; Wang, Meng-Jie; Xiong, Long-Wei; Li, Peng; Guo, Li-Ting; Wang, Meng-Yao; Peng, Dong-Hui; Lan, Si-Ren; Liu, Zhong-Jian (Plant molecular biology, 2023)
Cymbidium ensifolium is one of the national orchids in China, which has high ornamental value with changeable flower colors. To understand the formation mechanism of different flower colors of C. ensifolium , this research conducted transcriptome and metabolome analyses on four different colored sepals of C. ensifolium . Metabolome analysis detected 204 flavonoid metabolites, including 17 polyphenols, 27 anthocyanins, 75 flavones, 34 flavonols, 25 flavonoids, 18 flavanones, and 8 isoflavones. Among them, purple-red and red sepals contain a lot of anthocyanins, including cyanidin, pelargonin, and paeoniflorin, while yellow-green and white sepals have less anthocyanins detected, and their metabolites are mainly flavonols, flavanones and flavonoids. Transcriptome sequencing analysis showed that the expression levels of the anthocyanin biosynthetic enzyme genes in red and purple-red sepals were significantly higher than those in white and yellow-green sepals of C. ensifolium . The experimental results showed that CeF3′H2 , CeDFR , CeANS , CeF3H and CeUFGT1 may be the key genes involved in anthocyanin production in C. ensifolium sepals, and CeMYB104 has been proved to play an important role in the flower color formation of C. ensifolium . The results of transformation showed that the CeMYB104 is involved in the synthesis of anthocyanins and can form a purple-red color in the white perianth of Phalaenopsis . These findings provide a theoretical reference to understand the formation mechanism of flower color in C. ensifolium . Key message This study identified the differential metabolites and differential genes among different color sepals, determined the key regulatory genes, and constructed a regulatory network for the flower color formation of Cymbidium ensifolium .